Human Papillomavirus 16 E6 Antibodies in Individuals without Diagnosed Cancer: A Pooled Analysis - Lang Kuhs, Krystle A; Anantharaman, Devasena; Waterboer, Tim; Johansson, Mattias; Brennan, Paul; Michel, Angelika; Willhauck-Fleckenstein, Martina; Purdue, Mark P; Holcátová, Ivana; Ahrens, Wolfgang; Lagiou, Pagona; Polesel, Jerry; et al. (Cancer epidemiology, biomarkers & prevention, 2015)
BACKGROUND: The increasing incidence of oropharyngeal cancer in many developed countries has been attributed to human papillomavirus type 16 (HPV16) infections. Recently, HPV16 E6 serology has been identified as a promising early marker for oropharyngeal cancer. Therefore, characterization of HPV16 E6 seropositivity among individuals without cancer is warranted. METHODS: A total of 4,666 controls were pooled from several studies of cancer and HPV seropositivity, all tested within the same laboratory. HPV16 E6 seropositive controls were classified as having (i) moderate [mean fluorescent intensity (MFI) ≥ 484 and <1,000] or (ii) high seroreactivity (MFI ≥ 1,000). Associations of moderate and high HPV16 E6 seroreactivity with (i) demographic risk factors; and seropositivity for (ii) other HPV16 proteins (E1, E2, E4, E7, and L1), and (iii) E6 proteins from non-HPV16 types (HPV6, 11, 18, 31, 33, 45, and 52) were evaluated. RESULTS: Thirty-two (0.7%) HPV16 E6 seropositive controls were identified; 17 (0.4%) with moderate and 15 (0.3%) with high seroreactivity. High HPV16 E6 seroreactivity was associated with former smoking [odds ratio (OR), 5.5; 95% confidence interval (CI), 1.2-51.8], and seropositivity against HPV16 L1 (OR, 4.8; 95% CI, 1.3-15.4); E2 (OR, 7.7; 95% CI, 1.4-29.1); multiple HPV16 proteins (OR, 25.3; 95% CI, 2.6-119.6 for three HPV16 proteins beside E6) and HPV33 E6 (OR, 17.7; 95% CI, 1.9-81.8). No associations were observed with moderate HPV16 E6 seroreactivity. CONCLUSIONS: High HPV16 E6 seroreactivity is rare among individuals without diagnosed cancer and was not explained by demographic factors. IMPACT: Some HPV16 E6 seropositive individuals without diagnosed HPV-driven cancer, especially those with seropositivity against other HPV16 proteins, may harbor a biologically relevant HPV16 infection.
Keywords: Young Adult; represorové proteiny; Male; kohortové studie; protilátky virové; Risk Factors; mladý dospělý; Cohort Studies; onkogenní proteiny virové; infekce papilomavirem; Papillomavirus Infections; Adult; Aged; dospělí; Case-Control Studies; mužské pohlaví; senioři; nádory orofaryngu; ELISA; Human papillomavirus 16; lidský papilomavirus 16; senioři nad 80 let; Enzyme-Linked Immunosorbent Assay; lidé; ženské pohlaví; studie případů a kontrol; Humans; Oropharyngeal Neoplasms; rizikové faktory; Aged, 80 and over; Repressor Proteins; Antibodies, Viral; spinocelulární karcinom; Female; lidé středního věku; Oncogene Proteins, Viral; Carcinoma, Squamous Cell; Middle Aged